Effect of glucosaminyl muramyl dipeptide on cell-mediated immune response against fowl-pox - Pandit, Farhat; Mishra, S C; Jaiswal, T N (The Indian Journal of Animal Sciences, 2012)
Role of glucosaminyl muramyl dipeptide (GMDP) on cell-mediated immune response (CMIR) in chicken vaccinated with fowl-poxvaccine was studied using leucocyte migration inhibition test (LMIT) and skin reactive factor (SRF). Mean per cent migrationinhibition (% MI) was highest on 21 day post-vaccination with mean values of 65.00 in fowlpox vaccinated group and 70.25 inGMDP and fowl-pox vaccinated group. Higher value Â of MI in GMDP and fowl-pox vaccinated group indicates immunostimulatoryeffect of GMDP on CMIR. An intense SRF was detected at 24 hr post-inoculation of lymphokines indicating delayed typehypersensitivity reaction. Highest SRF values of 7.2 mm was found on 21st day post-vaccination with GMDP and fowl-pox incomparison to the value of 5.2 mm in fowl-pox group giving an evidence of immunostimulatory effect of GMDP on cell-mediatedimmune response. Histopathological examinations of guineapig skin sections revealed maximum cellular reactions at 24 hrpost-inoculation of lymphokines. Oedema with few polymorphonuclear cells and predominant infiltration of mononuclear cellsgives evidence of delayed type of hypersensitivity reactions indicating involvement of cell-mediated immune response.